PHILOSOPHY OF SCIENCE IN ENGINEERING EDUCATION: A PRACTICE!ORIENTED APPROACH - Natalya I. Martishina (Высшее образование в России, 2022)
The key theme of the article is the necessity of the classical course of the philosophy of science for training of a future researcher and engineer. Main focus is given to the operational re-orientation of this discipline. The basic functions of the philosophical course in the structure of post-graduate education program for engineers are designated. The methods of sampling and interpretation of educational material aimed at the implementation of a practice-oriented approach are offered.